Brexit, uncertainty, and migration decisions - Daniel Auer; Daniel Tetlow (International Migration, 2022)
We leverage the British Brexit referendum decision to leave the European Union, to demonstrate how changes in uncertainty about a country's future socio-political condition can impact migratory behaviour. Using official bilateral migration statistics, we report an excess increase in migration from the UK to the EU of approximately 16% post-referendum, compared to movements between the remaining EU countries over the same period. In addition, we analyse in-depth interviews conducted with UK migrants in Germany to show that uncertainty about future bilateral relations, a negative economic outlook, and perceptions of negative social consequences in the UK have been by far the most dominant drivers of migration in the post-referendum period. We further corroborate the effect of changes in uncertainty on migration-related behaviour with exceptional spikes in naturalisations, indicating that UK citizens living in other EU member states are actively taking decisions to mitigate the negative impact that Brexit is having on their livelihoods.
Keywords: 300